Burden and disease pathogenesis of influenza and other respiratory viruses in diabetic patients. Issue 4 (April 2022) - Thomas, Swapna; Ouhtit, Allal; Al Khatib, Hebah A.; Eid, Ali H.; Mathew, Shilu; Nasrallah, Gheyath K.; Emara, Mohamed M.; Al Maslamani, Muna A.; Yassine, Hadi M.
Abstract: Over the past two decades, diabetes mellitus (DM) has been receiving increasing attention among autoimmune diseases. The prevalence of type 1 and type 2 diabetes has increased rapidly and has become one of the leading causes of death worldwide. Therefore, a better understanding of the genetic and environmental risk factors that trigger the onset of DM would help develop more efficient therapeutics and preventive measures. The role and mechanism of respiratory viruses in inducing autoimmunity have been frequently reported. On the other hand, the association of DM with respiratory infections might result in severe complications or even death. Since influenza is the most common respiratory infection, DM patients experience disease severity and increased hospitalization during influenza season. Vaccinating diabetic patients against influenza would significantly reduce hospitalization due to disease severity. However, recent studies also report the role of viral vaccines in inducing autoimmunity, specifically diabetes. This review reports causes of diabetes, including genetic and viral factors, with a special focus on respiratory viruses. We further brief the burden of influenza-associated complications and the effectiveness of the influenza vaccine in DM patients.